Cultural and linguistic responsiveness in long-term care: A scoping review protocol on programs for residents and staff - Wenting Yan; Carmel L. Montgomery; Liz Dennett; Stephanie A. Chamberlain (PLoS ONE, 2026)
Background The demographic landscape of Western countries has shifted to a more diverse one. Along with the trend of an aging population, a new problem has emerged, which is the increased linguistic diversity in the aging population in these countries. As people age and their care needs increase, they may not receive optimal care if they don’t speak the same language as their caregivers in long-term care facilities. Culturally and linguistically responsive long-term care services are important to ensure the best care for an aging population, but there is limited evidence in the literature on the scope and practice of these services. The objective of this scoping review is to map out the types of CLR programs in LTC settings and examine their core components and target populations. Methods The Arksey and O’Malley framework, further developed by Levac and colleagues, will be employed in this scoping review. The research question was framed using the PCC framework. A comprehensive systematic search was developed with an experienced librarian and will be conducted in Scopus, CINAHL, Embase, Medline, PsycINFO, and Academic Search Complete. All primary study designs, including quantitative, qualitative, and mixed methods, will be included. Studies must focus on culturally and linguistically responsive care programs used or implemented in long-term care services. There will be no date or language limitations. Findings will be thematically synthesized to answer the research question. Conclusion This review protocol provides a transparent process for how it will be conducted. We aim to contribute to a better understanding of what culturally and linguistically responsive care programs exist, how cultural and linguistic responsiveness is currently addressed across diverse care environments, and what gaps remain in long-term care.